The Impact of Bank Finance on SME Export Activities: Updated Empirical Insights - Denny Saputera; Neneng Susanti; Sakina Ichsani (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
External capital is a vital resource for businesses seeking to enter international trade, with smaller firms being particularly dependent on it. Yet financial obstacles frequently prevent many SMEs from successfully breaking into export activities. This study investigates the impact of bank finance on SMEs’ export participation using firm-level data and empirical econometric analysis. The analysis employs descriptive statistics, correlation analysis, and regression estimation to assess the relationship between bank financing and export activities while controlling for firm-specific characteristics such as firm age, output, profitability, firm size, and human capital. The empirical results indicate a positive and statistically significant effect of bank finance on SMEs’ export participation. Firms with greater access to bank financing are better equipped to overcome financial barriers related to export activities, including production expansion, compliance with international standards, and logistics costs. Furthermore, firm output and firm size are found to positively influence export engagement, suggesting that productive capacity and scale are significant determinants of international market entry. These findings underscore the critical role of financial institutions in supporting SME internationalization. The study contributes to the literature on finance and international trade by addressing empirical evidence on how improved access to finance can facilitate international market entry for SMEs. Bank finance can enhance SMEs’ export performance and competitiveness in global markets.